Pengaruh Perlit Lampung sebagai Material Agregat Mortar Terhadap Kuat Tekan - Bramantyo Bayu Aji; Via Apri Setiani; Muhammad Amin; Syafriadi User (Inovasi Pembangunan : Jurnal Kelitbangan, 2018)
This research was conducted to find out the effect of Lampung perlite which used as mortar aggregate material against compressive strength. Perlite used is the mesh size 40. Variations of composition used are 1: 2, 1: 3, 1: 4 and 1: 5 (cement: perlite). Analyzes conducted include water content, specific gravity, mud content, absorption and characterization of X-Ray Fluorescence (XRF). The test is a compressive strength test with a 14 day test life. The result of raw material analysis shows that the perlite meets the standard as a mortar aggregate material and has a high Si content of 57.06%. The best compressive strength is obtained on mortar with a 1: 2 (cement 1: perlite 2) composition of 156.8 kg/cm2. The compressive strength of the mortar decreased with increasing number of perlite in 1: 3, 1: 4 and 1: 5 compositions with a compressive strength value of 84 kg/cm2, 70 kg/cm2 and 33.6 kg/cm2, respectively. This decrease is caused by excessive SiO2 content so that it binds to the free CaO contained in the cement and forms Ca(OH)2. Ca(OH)2 causes the mortar density to decrease and result in the formation of air cavities.